Contribution of Journalistic Infographic for Health Communication - Machado Velho, Ana Paula; Soares Dias Vermelho, Sônia Cristina; Durval Dorne, Vinícius (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2016)
The purpose of this article is to point out how the computer graphics can contribute to the organization of reports on health in printed vehicles, contributing to the strengthening area of health communication. To show it, the second year students of Journalism an educational institution of Maringá-Paraná-Brazil, who attended the course Graph Planning, were asked to analyze the design of a page of a brazillian newspaper Folha de S. Paulo, which was included a computer graphics. We have seen that this journalistic language offers several possibilities to Communication and Health Promotion, because joins verbal and imagery to arrest the content, helping change people habits from the moment that are increasingly present in the mass communication vehicles.